Customer satisfaction index at Radak Adventure Camp : facilites and services - Abdul Yaser, Mohamad Amar Akmal (2019)
Facilities and services are considered as the basic needs of the tourist when they are visiting a place of interest to them. Therefore, understanding their level of satisfaction are important to improve and provide better facilities and services. The study identifies the satisfaction level towards the facilities and services at Radak Adventure Camp, Gopeng, Perak. The study also compared the satisfaction level based on the socio-demographic and trip characteristics of the respondents. A total of 100 visitors answered the questionnaire during the data collection that was conducted in January and February of 2019. Descriptive analysis, satisfaction index (SI), t-test analysis, and Chi-square were used to analyze the data. Results shows that, most visitors were satisfied with the facilities and services provided at Radak Adventure Camp. Gender, nationality and frequency of visits are significant socio-demographic and trip characteristics that influenced satisfaction level among visitors. It was recommended that, the management will need to manage and maintains the facilities to increase the number of repeat visitors and improve services to increase satisfaction level among the visitors. Specifically, the management of the place will need to improve the facilities and services for more comfortable of the visitor and increase the visitor satisfaction level.